Charakter prawny zaświadczeń wydawanych przez podmioty prywatne oraz procedura ich wydawania - Główczewska, Aleksandra; Zawacka-Klonowska, Dominika (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The study analyses the views of doctrine and jurisprudence of administrative and common courts in order to resolve the issue of passing certificates by private entities. The authors have attempted to classify the private certificates and the mode of its issuance. The aim of the study was to indicate the obligation of private entities to pass the certificate at the request of the entitled person and the issue of legally protecting that person.
Keywords: certificate; private entity; mode of private certificates issuance; mode of passing certificates